Effects of Pancreatic Omentoplasty on Diabetes Mellitus with Obesity after Sleeve Gastrectomy: An In Vivo Study - Indra Kusuma Adi Putranto; K. Heri Nugroho; Abdul Mughni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: DM, especially type 2 diabetes mellitus (DMT2), is closely related to obesity. Insulin resistance and inflammation that occur in obese patients can be treated with SG procedures. Post-SG weight loss can reduce the lipo apoptotic process and can improve the function of pancreas β cells. The omentum is rich in potential mesenchymal stem cells and is rich in anti-inflammatory cytokines, and various growth factors, so the omentoplasty procedure is believed to be able to provide a regenerating effect on the pancreatic tissue so that the performance of the pancreas can be optimal. Methods: An experimental study with 18 rats which were divided into control and treatment groups. The treatments were sleeve gastrectomy and pancreatic omentoplasty. Furthermore, analysis of body weight and levels of IL-10 and HOMA IR was carried out with the help of SPSS software version 25 univariate and bivariate. Results: There was a difference in mean body weight, levels of IL-10, and HOMA IR before and after treatment, p<0.001. Conclusion: Omentoplasty is effective in improving the condition of diabetes mellitus with obesity after sleeve gastrectomy surgery in vivo.